Income inequality in Europe: What role does gender inequality play? - Agnieszka Gehringer; Stephan Klasen; Carlos Villalobos Barría (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2020)
Given the demographic structure of the population of the European countries, this paper examines how gender gaps in earned and non-earned income contribute to explain between household income inequality. We show that this impact depends not only on the existing gender gaps but also on the way how they are jointly distributed across the income distribution. Using the 2010 EU-SILC data, we propose a novel methodology that allows assessing the way in which gender gaps in income per adult, participation, labor earnings, hourly earnings, working hours, and in non-earned income affect inequality levels. We find an empirically discrete relationship between gender gaps and income inequality. Although this relationship tends to work differently across country groups (Western, Southern, Scandinavian, and Former Communist Economies), it is empirically not obvious which types of gender gaps are particularly relevant to determine the inequality level of the income distribution. A remarkable result is that the elimination of the gender gap in non-earned income tends to reduce the income inequality levels in a significant way in almost all European countries. This result suggests that there is a large space for reducing income inequality while improving the gender balance public and private transfers.
Keywords: J16; D63; 330; Gender Inequality; Gender Gaps; Household Income Inequality; Gini Coefficient; Microsimulations; Decomposition Technique